Tourism As An Emerging Economic Driver: Analyzing Sector Competitiveness And Growth Potential In Tana Toraja Regency, Indonesia (International Journal of Environmental Sciences, 2025)
Tourism has emerged as a significant economic driver in developing regions, particularly in areas with unique cultural heritage. Tana Toraja Regency, renowned for its distinctive funeral ceremonies, traditional architecture, and cultural landscapes, represents an important case study for understanding tourism's contribution to regional economic development in Indonesia. This study analyzes the contribution of the tourism sector to GDP growth in Tana Toraja Regency from 2014 to 2023, examining its competitive position and development potential within the regional economic structure. The research employs quantitative analysis using secondary data from Statistics Indonesia (BPS) covering the period 2014-2023. Location Quotient (LQ) analysis identifies base and non-base sectors, while Shift Share Analysis examines tourism sector growth dynamics through regional share, proportional shift, and competitive shift components. Comparative analysis with Badung and Sleman regencies provides benchmarking insights for tourism development strategies. The tourism sector, represented by accommodation and food services, demonstrates emerging base sector characteristics with an LQ value of 1.03, indicating comparative advantages but early development stage. Shift Share Analysis reveals positive competitive advantages with differential shift of 4.35 billion rupiah, showing genuine local competitive strengths. Despite ranking 12th among 17 economic sectors, the tourism sector exhibits all-positive shift share components, suggesting strong development potential. Comparative analysis shows significant gaps with established destinations: Tana Toraja contributes 1.46% to regional GDP compared to Sleman's 24.94% and Badung's 10.16%. Tourism sector in Tana Toraja shows emerging competitiveness with substantial untapped potential. Strategic interventions focusing on infrastructure development, human capital enhancement, cultural product development, and cross-sector collaboration can optimize tourism's contribution to regional economic growth.